2014
DOI: 10.1063/1.4892042
|View full text |Cite
|
Sign up to set email alerts
|

Cryogenic Joule annealing induced large magnetic field response of Co-based microwires for giant magneto-impedance sensor applications

Abstract: We have presented herein the results of microstructure, surface magnetic domains (SMDs), and giant magneto-impedance (GMI) effect of melt-extracted Co68.15Fe4.35Si12.25B11.25Nb2Cu2 amorphous wires for the first time employed by using a cryogenic Joule annealing (CJA) technique with large DC current amplitude. Compared with the conventional JA method, experimental results indicate that the maximum GMI ratio [ΔZ/Z0]max achieves up to 425% at 8.1 MHz with monotonic increase of the axial magnetic field Hex up to 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…Notch-defects may be resulted from the residual stress and distribution of magnetic charge, while antinotch-defects region (II) of Fig. 9c may be induced by the existence of zirconium atoms which are favor to form atomic clusters [28]. The defects existence on surface circumferential magnetic domains will reduce the circumferential permeability, which is provide closely associating with the GMI effect [29].…”
Section: Resultsmentioning
confidence: 97%
“…Notch-defects may be resulted from the residual stress and distribution of magnetic charge, while antinotch-defects region (II) of Fig. 9c may be induced by the existence of zirconium atoms which are favor to form atomic clusters [28]. The defects existence on surface circumferential magnetic domains will reduce the circumferential permeability, which is provide closely associating with the GMI effect [29].…”
Section: Resultsmentioning
confidence: 97%
“…Naturally it is realized that their microwave response could be more controllable and sensitive to external stimuli providing moderate wire treatment is done before embedding into the matrix. Recently, it has been reported that several emerging techniques including the combined current-modulation annealing (CCMA) [34], twin zone Joule annealing [35] and cryogenic Joule annealing [36] can significantly enhance the GMI effect and field sensitivity of Co-based microwires. Hence we believe that enhanced field/stress/current sensitivity in addition to other unique physics will be realized by performing such tailoring techniques to microwires prior to incorporating them into polymer context.…”
Section: Discussionmentioning
confidence: 99%
“…The result of the coupling effect leads to the unique surface domain structure of the microwire. The phenomenon that the response of the ΔX/X (%) obviously hysteretic to the ΔZ/Z (%) nearly 1.2 Oe is resulting from the crystallization of inner part due to the over Joule heat under large current while the outer-shell part keeping amorphous microstructure owing to the protection of liquid nitrogen 11 . In this case, the induced circumferential fields observed for the ΔX/X (%) curves after 300 mA CJA appear a large platform without sharp peak which corresponding to the response field H ex .…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, the Joule heat generated by CJA is enough to meet the atoms redistribution or crystallization 13 . However, the cool role of the liquid nitrogen around the microwire protects the surface amorphous microstructure against crystallization or oxidation during CJA process 11 . Moreover, it restrains the formation of surface domain rotation.…”
Section: Resultsmentioning
confidence: 99%